Fruit maturity and associated changes in Khasi mandarin (Citrus reticulata) at different altitudes in humid tropical climate - DESHMUKH, N A; PATEL, R K; RYMBAI, H; JHA, A K; DEKA, BIDYUT C (The Indian Journal of Agricultural Sciences, 2016)
Fruit maturity and associated changes in terms of physicochemical and sensorial qualities of Khasi mandarin (Citrus reticulat Blanco) grown at different altitudes, viz. 500-600 m, 700-800 m, 900-1 000 m and 1 300-1 400 m were studied under humid tropical climate of Meghalaya. Rapid increase in fruit growth was recorded from fruit development to colour break stage, however it was slow thereafter at all the altitudes. At 500-600m and 700-800m, juice yield was recorded highest at fruit maturity stage (46.64% and 49.11%) while, it was highest in advanced fruit maturity stage (50.90% and 51.15%) at 900-1 000 m and 1 300-1 400 m. Diurnal variation in climate stimulated drop in chlorophyll (‘a’, ‘b’ and total) and promoted development of yellowish orange colouration on fruit peel at altitude of 500-600 m and 700-800 m while deep orange colouration at 900-1 000 m and 1 300-1 400 m. Significant rise in TSS and TSS: acid ratio with drop in titratable acidity were recorded during maturation. Ascorbic acid content was recorded maximum at 1 300-1 400 m (44.13 mg/100 g) and 900-1 000 m (41.05 mg/100 g) compared with 700-800 m (37.56 mg/ 100 g) and 500-600 m (35.66 mg/100 g) at advanced maturity stage. Duration of 1 and 1 ½ month (fruit development to colour break stage) represents maturation at 500-600 m and 700-800 m considering TSS (10.23 °B and 10.13 °B), TSS: acid ratio (13.22 and 12.60), sweetness (3.93 and 3.67), flavour (8.00 and 7.93) and appearance (8.07 and 7.87) score. While duration of 2 and 2 ½ months (fruit development to fruit maturity stage) required at 900-1 000 m and 1 300-1 400 m considering TSS (10.07 °B and 10.16 °B), TSS: acid ratio (12.40 and 12.02), sweetness (4.07 and 3.93), flavour (7.87 and 7.93) and appearance (7.93 and 8.00) score.